Entre oasis y desierto - Amelina Correa Ramón (Mélanges de la Casa de Velázquez)
This article reviews the image of Morocco reflected in the Spanish literature of the late 19th and early 20th centuries, with particular emphasis on narrative. That image fluctuated between an idealised recreation, filtered through writings and artistic portrayals that presented Morocco as a species of mythical Orient in the manner of a timeless paradise, and a much more critical vision, assuredly influenced by the stormy relations prevailing between Spain and Morocco during those decades.